Interação empresa-usuário/a na economia criativa: uma análise da comunicação de uma empresa líder no mercado de tv pela internet - Becker, Manoela Junqueira (Universidade do Vale do Rio dos Sinos, 2016)
This paper is about the interaction between companies of the Creative Economy and their customers or potential customers, more specifically on the Facebook. The purpose is to understand what is the Creative Economy, which areas are part of this Economy and what is their peculiarities. Understanding how the interaction with the client may be a way to approach and relationship maintenance. The focus of the research is to analyze the role and importance of the Facebook page of Company A, leader in Internet TV market, for the development of their relationship with their customers or potential customers, based on postings from July 2016. From the literature, it is presents the concept of Creative Economy, customer relationship, online communication, social media, social networking sites and consumer behavior. Next, a case study is presented with the results of analysis. The methodology used is qualitative, descriptive and exploratory. After the analysis, it is clear that Company A uses their Facebook page to engage their audience through different content types, in order to inform and interact with their fan, and reach values as visibility, popularity and reputation.
Keywords: Economia criativa; Relacionamento com o cliente; Redes sociais; Comunicação; Facebook; Creative economy; Customer relationship; Social media; Communication